Increasing oat stability through germination and drying - Heiniö, Raija-Liisa; Lehtinen, Pekka; Oksman-Caldentey, Kirsi-Marja; Poutanen, Kaisa (MTT, 2004)
Oat is palatable, beneficial to one's health, it has advantageous lipid composition and valuable technical properties related to forming viscosity. However, due to the high fat content, a rancid and bitter flavour develop easily in oat during storage, and forms thus an obstacle for the use. A germination-drying process has shown nicely to adjust the perceived flavour (Heiniö et al. 2001), and was now applied before storing oat, the aim being to increase. the stability. Changes in sensory attributes determined by descriptive profiling, lipid composition and amounts of volatile and phenolic compounds of native and processed (germinated, dried) crushed oat were followed during a 12 month storage period. The influence of the chemical attributes on the sensory profiles of oats was analysed statistically by PLS regression. The sensory profiles of the native and processed oat groats changed significantly during the storage period, and chemical changes causing rancidity and bitterness developed more slowly in the processed oat as compared to the native oat (Heiniö et al. 2002). The most intensive changes due to deterioration had already occurred after one month of storage in native oat, whereas in processed oat these changes were perceived several months later. Stored, deteriorated oat was assessed as having musty, earthy odour and bitter, rancid flavour. These sensory attributes were closely correlated to free fatty acids and volatile compounds related to lipid oxidation. By contrast, total amount of phenolic compounds and volatile compounds derived mainly from protein degradation were highly related to favourable roasted odour and flavor. Thus, stability of oat groats can be significantly increased through germination and subsequent heat-treatment. Heiniö, R.-L. et al. 2001. Cereal Chemistry 6: 707-714; Heiniö, R.-L. et al. 2002. Cereal Chemistry 3: 367-375.
Keywords: Ka; Oat; germination; storage; rancid & bitter flavour; lipid; volatile